2004
DOI: 10.1063/1.1783011
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and phase transformations in amorphous NiTi thin films for microelectromechanical systems

Abstract: Amorphous sputtered nickel–titanium thin films were deposited onto micromachined silicon-nitride membranes and subjected to heating and cooling conditions. Their associated microstructure was monitored directly and simultaneously with in situ transmission electron microscopy. These electron-transparent membranes constrained the NiTi films and rendered it possible for observation of the complete transformation cycle, which includes: the crystallization of the amorphous phase to austenite phase (cubic B2 structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 12 publications
5
35
1
3
Order By: Relevance
“…This process was re-done multiple times and the formation of the metastable phase is repeatable. Isothermal keeping the specimen for several minutes, the metastable TiNi phase The morphological features of the crystallized phase in study 5) are similar to the present study while there was no intermediate phase reported in that study. The reason of absence of the intermediate phase in study 5) may come from two reasons: firstly the specimen was kept at the temperature of 470 C for too long and the intermediate phase transformed to the stable B2 phase quickly and secondly, the intermediate phase only appears in a range of composition and it excludes the composition of study.…”
Section: Polymorphous Homogenous Nucleation In the Thick Regionssupporting
confidence: 86%
See 3 more Smart Citations
“…This process was re-done multiple times and the formation of the metastable phase is repeatable. Isothermal keeping the specimen for several minutes, the metastable TiNi phase The morphological features of the crystallized phase in study 5) are similar to the present study while there was no intermediate phase reported in that study. The reason of absence of the intermediate phase in study 5) may come from two reasons: firstly the specimen was kept at the temperature of 470 C for too long and the intermediate phase transformed to the stable B2 phase quickly and secondly, the intermediate phase only appears in a range of composition and it excludes the composition of study.…”
Section: Polymorphous Homogenous Nucleation In the Thick Regionssupporting
confidence: 86%
“…Isothermal keeping the specimen for several minutes, the metastable TiNi phase The morphological features of the crystallized phase in study 5) are similar to the present study while there was no intermediate phase reported in that study. The reason of absence of the intermediate phase in study 5) may come from two reasons: firstly the specimen was kept at the temperature of 470 C for too long and the intermediate phase transformed to the stable B2 phase quickly and secondly, the intermediate phase only appears in a range of composition and it excludes the composition of study. 5) As studied by the composite EDPs analysis on the intermediate phase, the crystal structure can be determined to be cubic with lattice parameter of a ¼ 0:903 nm which is 3 times of the stable B2 phase.…”
Section: Polymorphous Homogenous Nucleation In the Thick Regionssupporting
confidence: 86%
See 2 more Smart Citations
“…One prominent example is the size effect that can significantly shift the transformation from the cubic B2 high temperature phase to the monoclinic B19' martensite; grains with a size less than 50 nm can even lead to the complete suppression of the transformation [15,16]. [17][18][19][20], melt spinning (MS) [21][22][23][24] and cold rolling [25,26].…”
Section: Introductionmentioning
confidence: 99%